Current understanding of LRRK2 in Parkinson's disease: biochemical and structural features and inhibitor design. (September 2012) - Ray, Soumya; Liu, Min
Since leucine-rich repeat kinase 2 (LRRK2) was linked to Parkinson's disease in 2004, kinase activity of LRRK2 has been believed to play a critical role in the pathogenesis of Parkinson's disease. As a result, identification of LRRK2 inhibitors has been a focus for drug discovery. However, most LRRK2 mutations do not simply increase kinase activity. In this review we summarize the potential mechanisms that regulate the kinase activity of LRRK2. We outline some currently available kinase inhibitors, including the identification of a DFG-out (type-II) inhibitor. Finally, we discuss the relationship of LRRK2 with tau and α-synuclein. The fact that all three proteins are autophapgy-related provides a future strategy for the identification of LRRK2 physiological substrate(s).